Determination of an unstability area of a system by using the expansion of a n-th order determinant by k-th order determinants - Kavaliauskas, Algis (Lietuvos matematikos rinkinys, 2001)
The article deals with a proof of a formula, devoted to expansion of a determinant by any of k rows and k columns. By its help the area of unstability in a electromechanical system can be determined.